Plasma complement biomarkers distinguish multiple sclerosis and neuromyelitis optica spectrum disorder. (June 2017) - Hakobyan, Svetlana; Luppe, Sebastian; Evans, David RS; Harding, Katharine; Loveless, Samantha; Robertson, Neil P; Morgan, B Paul
Background: Multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) are autoimmune inflammatory demyelinating diseases of the central nervous system. Although distinguished by clinicoradiological and demographic features, early manifestations can be similar complicating management. Antibodies against aquaporin-4 support the diagnosis of NMOSD but are negative in some patients. Therefore, there is unmet need for biomarkers that enable early diagnosis and disease-specific intervention. Objective: We investigated whether plasma complement proteins are altered in MS and NMOSD and provide biomarkers that distinguish these diseases. Methods: Plasma from 54 NMOSD, 40 MS and 69 control donors was tested in multiplex assays measuring complement activation products and proteins. Using logistic regression, we tested whether combinations of complement analytes distinguished NMOSD from controls and MS. Results: All activation products were elevated in NMOSD compared to either control or MS. Four complement proteins (C1inh, C1s, C5 and FH) were higher in NMOSD compared to MS or controls. A model comprising C1inh and terminal complement complex (TCC) distinguished NMOSD from MS (area under the curve (AUC): 0.98), while C1inh and C5 distinguished NMOSD from controls (AUC: 0.94). Conclusion: NMOSD is distinguished from MS by plasma complement biomarkers. Selected complement analytes enable differential diagnosis. Findings support trials of anti-complement therapies in NMOSD.